Influenza A Outbreaks in Two Professional Ice Hockey Teams during COVID-19 Epidemic - Lindblad Niklas; Hänninen Timo; Valtonen Maarit; Heinonen Olli J.; Waris Matti; Ruuskanen Olli (MDPI, 2025)
Influenza A outbreaks occurred in two professional hockey teams just after two games they played against each other. Thirteen players and two staff members fell ill during 17–20 April 2022, while COVID-19 was prevalent. Altogether, seven players missed an important game due to influenza. The rapid diagnosis permitted effective pharmaceutical and nonpharmaceutical control of the outbreaks.